A CADAVERIC STUDY OF ANATOMICAL VARIATIONS IN THE THYROID GLAND - DR DEEPA G; DR SHRIKRISHNA B H (International Journal of Pharma and Bio Sciences, 2015)
The thyroid gland is the first endocrine gland to develop in the embryo. Developmental anomalies of thyroid gland are quiet commonly seen. Most of the variations are due to the partial persistence of the median or thyroglossal duct. Persistence of pyramidal lobe, thyroglossal cysts, agenesis of the thyroid gland and aberrant thyroid are the major developmental anomalies of the thyroid gland. We conducted a study in about 20 formalin fixed cadavers to look for any morphological variations of thyroid gland including pyramidal lobe and levator glandular thyroidae. All the anomalies detected were documented and compared with previous studies. The complete knowledge about thyroid anatomy, its variation and its associated anomalies is very important for surgeons for surgical interventions. It is also important for physicians and radiologists so that these variations are not overlooked in the differential diagnosis.